Optimalisasi padlet sebagai pemantik siswa dalam kreasi Kemis ngARTis - Maulana, Rizqi; Sukmayadi, Yudi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This article presents a program for optimizing the use of multimedia called padlet as a trigger for students' creativity to develop a variety of movements in domyak art. What was discussed was the process of revitalizing the domyak art which was brought to junior high schools in Purwakarta district. The material studied is a variety of tilu tapping movements in domyak art for SMP Negeri 1 Wanayasa. The type and method of research used is qualitative. Based on the analysis, it can be concluded that with the padlet application, students not only learn the art of various tap tilu movements, but also study the contextual problems of domyak dance in society, including the use of the padlet application as a student learning tool.